2019
DOI: 10.3390/agriculture9120256
|View full text |Cite
|
Sign up to set email alerts
|

Do Land Ownership and Agro-Ecological Location of Farmland Influence Adoption of Improved Rice Varieties? Evidence from Sierra Leone

Abstract: This study investigates the impact of farmland ownership and agro-ecological location on the adoption of the two most important sources of improved rice varieties (NERICA and ROK) in the context of Sierra Leone. In terms of farmland ownership, the results showed that farmers who cultivated their own land had a higher tendency of remaining as non-adopters of improved varieties, but those who rented farmland or were engaged in sharecropping had higher adoption rates of improved rice varieties. Also, the location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
4
7
0
Order By: Relevance
“…Thus, the few women (14% of respondents) engaged in rice production are more likely to follow the recommendation in terms of fertilizers and other inputs needed for better yield as they expect good financial gain. This finding corroborates those of Degefu [44] and Mansaray et al [45], who found that female-headed households were more likely to adopt improved inputs, in comparison with male-headed households in Ethiopia and Sierra Leone, respectively. Nevertheless, this finding contradicts the study of Nahayo et al [43], who reported that male farmers have more willingness to participate in crop intensification in Rwanda.…”
Section: Determinants Of Fisupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the few women (14% of respondents) engaged in rice production are more likely to follow the recommendation in terms of fertilizers and other inputs needed for better yield as they expect good financial gain. This finding corroborates those of Degefu [44] and Mansaray et al [45], who found that female-headed households were more likely to adopt improved inputs, in comparison with male-headed households in Ethiopia and Sierra Leone, respectively. Nevertheless, this finding contradicts the study of Nahayo et al [43], who reported that male farmers have more willingness to participate in crop intensification in Rwanda.…”
Section: Determinants Of Fisupporting
confidence: 90%
“…Indeed, the most educated rice farmers can easily understand the importance of fertilizer in rice farming and apply it as recommended by researchers. The positive influence of a high educational level on the adoption of improved inputs has been reported in previous studies carried out in Sierra Leone [45] and Nigeria [46].…”
Section: Determinants Of Fisupporting
confidence: 63%
See 2 more Smart Citations
“…Land ownership also stimulate the producer to invest in more demanding or long-term agricultural technologies than if not owned. However, these results disagreed with Mansaray et al (2019) and Mugumaarhahama et al (2021) who showed that farmers who cultivated their own land had a higher tendency of remaining non-adopters of improved varieties, but those who rented farmland or were engaged in sharecropping had higher adoption rates of improved rice and potato varieties to make the investment pro table. Access to agricultural credit positively and signi cantly in uenced the adoption of IMVs.…”
Section: Socio-economic Characteristics Of Maize Farmers In the South...mentioning
confidence: 59%